A documentation and analysis of project planning of a web-based interior designer (ID) platform - Pacaba, Richard John M.
Monochrome describes itself as "the newest startup set to disrupt the local design industry" in the Philippines. The team is composed of four freelance experts—an architect, a civil engineer, an IT specialist, and a businessman. Together, they strive to introduce innovations to the current interior design industry, both local and international. Monochrome currently offers traditional services, such as architectural and interior design, fit-out and construction, graphics, and 3D visualizations. The challenge is how. to transform it from a purely traditional design-and-build studio to a high technology-enabled startup.